Direct market valuation method to evaluate economic value of provisioning ecosystem services on household income in Zambia’s Bangweulu Wetland - Tembo, Greyford; Banda, Kawawa; Chundu, Misheck Lesa; Lyoba, Chisanga; Sichingabula, Henry; Nyambe, Imasiku (Frontiers in Environmental Science, 2025)
Wetlands are known to be one of the most productive and valuable ecosystems that provide important and diverse benefits to people around the world, contributing to provisioning, regulating, cultural and supporting services. However, very few studies have focused on the monetary value of provisioning ecosystem services and their contribution to household income. This paper aims to investigate the monetary value of provisioning services and their contribution to household income in the Bangweulu Wetland and surrounding areas, Zambia. A direct market valuation method was employed to quantify the products collected from the Bangweulu Wetland and surrounding areas and to assess their contribution to household income. Primary data, including household survey questionnaires, field observations, field measurements and key informant interviews, were employed. The research employed statistical techniques, including the estimation of mean frequencies, averages and the Pearson Chi-square test. Stratified random sampling was employed to sample 340 households in six districts. Also, purposive sampling was employed to sample seventeen key informants from government departments and traditional leaders. Major products collected include freshwater, crops, fish, woodfuel, grass, livestock rearing, reeds, papyrus, wild products and clay soil. However, freshwater had no significant monetary value and contributed minimally to household income. The Pearson Chi-square test showed that social factors such as gender, residential status, and house type significantly influenced the utilisation of various wetland resources, including crops, fish, woodfuel, reeds, papyrus and freshwater. In contrast, factors such as age, family size and employment level had no significant impact on resource utilisation. The gross monetary value of these services was estimated at US$ 11.7 million annually, the total cash income estimated at US$ 9.94 million and the total net monetary value estimated at US$ 10.5 million. Fishing and agriculture accounted for the largest contribution to household incomes (66.9% and 25.3%, respectively). These statistics underscore the critical role played by the Bangweulu Wetland in sustaining local livelihoods. Consequently, policymakers should carefully consider the economic value of the Bangweulu Wetland’s ecosystem services in their planning and as an integral part of potential poverty reduction strategies.